Program Pembuatan dan Penyuluhan Langsung Tempat Sampah Terpilah di Posyandu Kelurahan Penajam Kabupaten Penajam Paser Utara - Yuliana, Lina; Apriansyah, Apriansyah; Faza, Hesel Ananta Hasya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Waste management problems persist at the Integrated Health Post (Posyandu) in RT 16, Penajam Village, Penajam Paser Utara Regency. Waste from monthly activities has not been properly sorted and managed. This situation has the potential to cause environmental pollution, unpleasant odors, and health risks, especially for toddlers and the elderly. This community service program aims to provide separate waste bins and raise public awareness of proper waste management. The method used is a participatory approach through observation, planning, implementation, outreach, and evaluation. The activities included the construction of three types of separate waste bins (organic, inorganic, and hazardous waste) and outreach to the community and Posyandu cadres. The results of the activities show an increase in public understanding, as evidenced by the ability to sort waste according to type and increased participation in maintaining environmental cleanliness. The Posyandu environment has also become cleaner and more organized. This program not only provides physical facilities but also encourages changes in community behavior towards sustainable environmental management.